Euglycemic Diabetic Ketoacidosis in a Patient Post Cardiac Surgery Receiving Continuous Renal-Replacement Therapy - Walter Yaw Agyeman; Inemesit Akpan; Kwasi Opare-Addo; Saheed Soleye; Alfred Solomon (Annals of Internal Medicine: Clinical Cases)
Euglycemic diabetic ketoacidosis is an often-underrecognized endocrine emergency. We highlight an unusual presentation of euglycemic diabetic ketoacidosis in a patient with a history of hypertension, type 2 diabetes mellitus, and stage 3b chronic kidney disease who had elective aortic and mitral valve–replacement surgery. She developed acute kidney injury requiring temporary continuous renal-replacement therapy. Despite hemodialysis, the patient had persistent anion-gap metabolic acidosis. Additional evaluation resulted in the diagnosis of euglycemic diabetic ketoacidosis. Successful care in this patient population entails a high index of suspicion, early diagnosis, and appropriate management.